An updated systematic review and meta‐analysis of early outcomes after left atrial appendage occlusion. (1st March 2018) - Yerasi, Charan; Lazkani, Mohamad; Kolluru, Prathik; Miryala, Varun; Kim, Jae; Moole, Harsha; Sawant, Abhishek C.; Morris, Michael; Pershad, Ashish
Abstract : Background: Left atrial appendage occlusion (LAAO) is a promising intervention for stroke prevention in patients with non‐valvular atrial fibrillation (NVAF). Early outcomes following LAAO have been published in many studies with variable results. Objective: This updated meta‐analysis aims to provide a summary of the early outcomes of LAAO. Methods: Medline/Pubmed, Ovid Journals, Clinical trials, Abstract meetings, Cochrane databases were searched from January 1st, 1999 to November 30th, 2016. Results: This meta‐analysis included 49 studies involving 12 415 patients. The median age was 73.5 years (IQR 72‐75 years) and 43% were males. Hypertension and diabetes were present in 36% and 15% of the population, respectively. There was a prior history of stroke and congestive heart failure in 14% and 18% of the population, respectively. The median CHADS2 score was 2.9 (IQR 2.6‐3.3) and the median HASBLED score was 3.3 (IQR 3‐4). LAAO implantation was successful in 96.3% of patients (95.40‐97.08, I 2 = 76.1%). The pooled proportion of all‐cause mortality was 0.28% (0.19‐0.38, I 2 = 0%). The pooled proportion of all‐cause stroke was 0.31% (0.22‐0.42, I 2 = 9.4%), major bleeding requiring transfusion was 1.71% (1.13‐2.41, I 2 = 73.2%), and pericardial effusion was 3.25% (2.46‐4.14, I 2 = 79%). Sub analysis of randomized clinical trials comparing LAAO devices to warfarin showed lower mortality ( P = 0.03) with similar bleeding risk ( P = 0.20) with LAAO. Conclusions: This meta‐analysis concludes that LAAO occlusion is a safe and effective stroke prevention strategy in patients with NVAF.